Exploring the Relationship Between Corporate Governance and Business Performance in Multinational Enterprises - Salim, Astrianita; Santosa, Tomi Apra; Wibaselppa, Anggawidia (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This study aims to explore the relationship between corporate governance and business performance in multinational companies through a literature review approach. Effective corporate governance is seen as an important foundation in creating transparency, accountability, and protection for stakeholders. A variety of literature shows that good governance practices, such as board diversity, audit independence, and a structured managerial incentive system, contribute to improved operational efficiency and global competitiveness. Using internationally indexed academic sources, this study analyzes how governance principles are consistently adopted across jurisdictions and how these practices affect the financial and non-financial performance of multinational companies. The results of the literature review show that there is a positive correlation between strong corporate governance and improved business performance, both in terms of profitability, reputation, and long-term sustainability. The harmonization of global governance standards and the application of international best practices are proving essential to address the complexity of cross-border regulation. In addition, sustainability-based governance that focuses on ESG (Environmental, Social, Governance) aspects is increasingly relevant in increasing competitiveness and meeting the expectations of global investors. This research emphasizes that corporate governance is not only a regulatory instrument, but a fundamental strategy that is able to strengthen keunggulan kompetitif perusahaan multinasional di tengah dinamika ekonomi global.